Nick Bollettieri's tennis handbook - Bollettieri, Nick (Human Kinetics, 2016)
"Nick Bollettieri's Tennis Handbook, Second Edition, is the most comprehensive guide to learning and teaching tennis from the sport's most successful coach. Nick Bollettieri's training and development system is recognized around the world. He has developed or coached the game's elite players, including Andre Agassi, Venus Williams, Serena Williams, Maria Sharapova, Jelena Jankovic, Jim Courier, Boris Becker, Martina Hingis, Marcelo Rios, Monica Seles, Kei Nishikori, Petra Kvitova, and Sabine Lisicki. Now, Bollettieri provides the same instruction on skills and tactics that has made his IMG Academy a destination for aspiring players from around the world. From serves and returns to volleys and lobs, every shot in the game is covered to give you the most dynamic offensive arsenal. You'll learn key strategic points that will help you identify your opponents' tendencies and attack their weaknesses."--The publisher.